2004
DOI: 10.1113/expphysiol.2004.027706
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous changes in guinea‐pig respiratory pattern during barometric plethysmography: role of catecholamines and nitric oxide

Abstract: Barometric plethysmography for unrestrained animals is a non-invasive method that allows repetitive measurements of pulmonary function, but habituation of the conscious animal to this technique has not been explored. Respiratory frequency (f R ) and 'enhanced pause' (P enh ) were measured by barometric plethysmography for a period of 8 h in guinea-pigs. Compared with basal values, during the first hour of recording a progressive increase in P enh (up to 25-50%) and a corresponding decrease in f R were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…We found that Penh in rabbits had a progressive decrease in the first 60 min of recording. This is contrary to Penh changes occurring in guinea pigs during barometric plethysmography [10]. Thus, in guinea pigs, Penh values were relatively low immediately after the animal entered the chamber, but these were followed by a progressive increase in the next 90 min.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We found that Penh in rabbits had a progressive decrease in the first 60 min of recording. This is contrary to Penh changes occurring in guinea pigs during barometric plethysmography [10]. Thus, in guinea pigs, Penh values were relatively low immediately after the animal entered the chamber, but these were followed by a progressive increase in the next 90 min.…”
Section: Discussioncontrasting
confidence: 66%
“…This last method is remarkably useful due to its simplicity and because it allows the animal to stay in an unrestrained state and even to eat and drink at libitum. Some years ago, it was reported that guinea pigs submitted to barometric plethysmography have an initial period of adaptation to the confinement inside the plethysmographic chamber, which takes up to 90 min to stabilize [10]. Changes observed during this period were probably due to stress and consisted of a decreasing trend of respiratory frequency that was mirrored by an increasing trend in a surrogate of lung resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The dose–response curve was stopped when Penh reached three times its baseline level. Once Penh had returned close to the initial baseline value (<50% increment) [14], OVA challenge was administered. The second curve was performed 3 h after OVA challenge.…”
Section: Methodsmentioning
confidence: 99%
“…One hour after concluding the second histamine curve, and when at least 50% of baseline Penh was reached [14], animals were overdosed with an intraperitoneal injection of pentobarbital sodium (65 mg/kg) and the trachea was cannulated. Using a syringe, 5 mL of saline solution (37 °C) was introduced through the tracheal tube and gently recovered 1 min later.…”
Section: Methodsmentioning
confidence: 99%
“…Airway hyperresponsiveness was evaluated in sensitized animals from the 35 and 125 days model using 2 nebulized histamine dose-response curves, practiced prior and following an OVA challenge as previously described (31,32). In the guinea pig, histamine aerosol administration induces an all-or-none response (33).…”
Section: Methodsmentioning
confidence: 99%